Quantitative Cervical Spinal Cord 3T Proton MR Spectroscopy in Multiple Sclerosis - Marliani, A.F.; Clementi, V.; Albini Riccioli, L.; Agati, R.; Carpenzano, M.; Salvi, F.; Leonardi, M. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Brain proton MR spectroscopy (1H-MR spectroscopy) is a useful technique for evaluating neuronal/axonal damage and demyelization in multiple sclerosis (MS). Because MS disability is frequently related to spinal cord lesions, potential markers for MS stage differentiation and severity would require in vivo quantification of spinal integrity. However, few spectroscopy studies have investigated cervical disease due to technical difficulties. The present study used 3T 1H-MR spectroscopy to measure the main metabolites in cervical spinal cord plaques of a group in patients with relapsing-remitting MS (RRMS) and compared them with metabolite measurements in healthy volunteers. MATERIALS AND METHODS: A 1H-MR point-resolved spectroscopy sequence volume of interest was prescribed along the main axis of the cord between C2 and C3 levels on a plaque in a group of 15 patients with RRMS for a total acquisition time of approximately 14 minutes. MR spectroscopy data were analyzed by the user-independent fitting routine LCModel, and relative metabolite concentrations were expressed by the absolute concentration ratios. A Student t test was used to evaluate the difference compared with the healthy metabolite content previously published. RESULTS: We found a significant decrease of total N-acetylaspartate/choline and an increase in choline/creatine and myo-inositol/creatine content on MS plaques in comparison with healthy cervical spine tissue. CONCLUSIONS: In vivo 1H-MR spectroscopy, if confirmed by other similar studies, should be as reliable for clinical studies as it is in brain imaging. Moreover, 1H-MR spectroscopy allows examination of spinal cord integrity at a biochemical level and may be sensitive to subtle changes occurring during the course of MS disease.